Exponentially Stable Motion Control for Multirotor UAVs with Rotor Drag and Disturbance Compensation - Moeini, Amir; Lynch, Alan F.; Zhao, Qing (Journal of intelligent & robotic systems, 2021)
In this paper we propose a centralized disturbance observer-based integral-augmented backstepping nonlinear motion control for a multirotor unmanned aerial vehicle (UAV). The approach explicitly compensates for rotor drag forces. The control is termed centralized as it based on the full rigid body vehicle model (i.e., rotational and translational dynamics). The dynamic state feedback includes two disturbance observers which estimate external force and torque disturbances. The effect of rotor drag is compensated in the proposed force disturbance observer and the backstepping motion controller. The closed-loop dynamics is proven to be exponentially stable in the presence of constant disturbances. The proposed control is implemented on the open-source PX4 autopilot software and validated using a Software-in-the-loop (SITL) simulation. The simulation results demonstrate the method’s robustness and steady-state error performance. Rotor drag compensation is shown to improve the tracking error performance.